EVOLUTION OF CUISINE TERMINOLOGY ACROSS CULTURES - Cazacu, Parascovia; Saganean, Gabriela (CEP USM, 2023)
Cuisine terminology is an essential part of a cultural identity. The evolution of cuisine terminology refers to the changes that have occurred in the language used to describe food, cooking techniques, ingredients, and culinary traditions over time. It has been shaped by various factors, including globalization, migration, technology, and changing cultural attitudes toward food. Globalization has been a critical factor in the evolution of cuisine terminology, as it has brought people from different cultures together, leading to the introduction of new terms and vocabulary. By moving from one country to another, people have brought their food traditions and adapted them to the new surroundings. Similarly, technology has had a decisive influence on food distribution, leading to the introduction of new terms describing different types of food outlets. New definitions and terminology have been developed to describe the various kinds of food and eating habits, thanks to increasing health awareness and recognition of the environmental impact of food production. As these attitudes continue to evolve, cuisine terminology will likely continue to change and adapt to these changes. The evolution of cuisine terminology reflects the dynamic nature of our world and the diversity of our food traditions and practices. Moreover, it has given rise to a better understanding and appreciation of diverse cuisines, encouraging innovation and sustainability in the food industry as well as preserving culinary traditions and cultural heritage.

Terminologia bucătăriei este o parte esențială a unei identități culturale. Evoluția terminologiei culinare se referă la schimbările care au avut loc în limbajul folosit pentru a descrie mâncarea, tehnicile de gătit, ingredientele și tradițiile culinare de-a lungul timpului. Acesta a fost modelată de diverși factori, inclusiv globalizare, migrația, tehnologia și schimbarea atitudinilor culturale față de alimente. Globalizarea a fost un factor critic în evoluția terminologiei culinare, deoarece a reunit oameni din culturi diferite, ducând la introducerea de noi termeni și vocabular. În mod similar, tehnologia a avut o influență decisivă asupra distribuției alimentelor, ducând la introducerea de noi termeni care descriu diferite tipuri de magazine alimentare. Datorită creșterii conștientizării sănătății și recunoașterii impactului asupra mediului al producției alimentare, noi definiții și termeni au apărut pentru a descrie diferitele tipuri de alimente și obiceiuri culinare. Pe măsură ce aceste atitudini continuă să evolueze, terminologia bucătăriei va continua probabil să se schimbe și să se adapteze la aceste schimbări. Astfel, evoluția acestui tip de terminologie reflectă natura dinamică a lumii noastre și diversitatea tradițiilor și practicilor noastre culinare. Mai mult, ea a dat naștere la o mai bună înțelegere și apreciere a diverselor bucătării, încurajând inovația și sustenabilitatea în industria alimentară, precum și păstrarea tradițiilor culinare și a moștenirii culturale.
EVOLUȚIA TERMINOLOGIEI CULINARE ÎN DIFERITE CIVILIZAȚII
Keywords: terminology; diversitate; terminologie